Immunogenicity induced by the use of alternative vaccine platforms to deal with vaccine shortages in a low- to middle-income country: Results of two randomized clinical trials - Alejandro Macchia; Daniel Ferrante; María Belén Bouzas; Patricia Angeleri; Cristián Biscayart; Jorge Geffner; Lilia Mammana; Inés Zapiola; Eduardo Luis López; Angela Gentile; Augusto Varese; Ignacio Mazzitelli; et al. (Elsevier, 2022)
Summary: Background: Shortages of component two of Sputnik V vaccine (rAd5) are delaying the possibility of achieving full immunisation. The immunogenic response associated with the use of alternative schemes to complete the scheme was not explored. Methods: We did two non-inferiority randomized clinical trials with outcomes measures blinded to investigators on adults aged 21-65 years, vaccinated with a single dose of rAd26 ≥ 30 days before screening and no history of SARS-CoV-2. Participants were assigned (1:1:1:1:1) to receive either rAd5; ChAdOx1; rAd26; mRNA-1273 or BBIBP-CorV. The primary endpoint was the geometric mean ratio (GMR) of SARS-CoV-2 anti-spike IgG concentration at 28 days after the second dose, when comparing rAd26/rAd5 with rAd26/ChAdOx1, rAd26/rAd26, rAd26/mRNAmRNA-1273 and rAd26/BBIBP-CorV. Serum neutralizing capacity was evaluated using wild type SARS-CoV-2 reference strain 2019 B.1. The safety outcome was 28-day rate of serious adverse. The primary analysis included all participants who received ≥ 1 dose. The studies were registered with NCT04962906 and NCT05027672. Both trials were conducted in Buenos Aires, Argentina. Findings: Between July 6 and August 3, 2021, 540 individuals (age 56·7 [SD 7·3]; 243 (45%) women) were randomly assigned to received rAd5 (n=150); ChAdOx1 (n=150); rAd26 (N=87); mRNAmRNA-1273 (n=87) or BBIBP-CorV (n=65). 524 participants completed the study. As compared with rAd26/rAd5 (1·00), the GMR (95%CI) at day 28 was 0·65 (0·51-0·84) among those who received ChAdOx1; 0·47 (0·34-0·66) in rAd5; 3·53 (2·68-4·65) in mRNA-1273 and 0·23 (0·16-0·33) in BBIBP-CorV. The geometric mean (IU/ml) from baseline to day 28 within each group increased significantly with ChAdOx1 (4·08 (3·07-5·43)); rAd26 (2·69 (1·76-4·11)); mRNA-1273 (21·98 (15·45-31·08)) but not in BBIBP-CorV (1·22 (0·80-1·87)). Interpretation: Except for mRNA-1273 which proved superior, in all other alternatives non-inferiority was rejected. Antibody concentration increased in all non-replicating viral vector and RNA platforms. Funding: The trials were supported (including funding, material support in the form of vaccines and testing supplies) by the Buenos Aires City Government.